2014
DOI: 10.1007/s00595-014-0966-5
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment in the management of idiopathic granulomatous mastitis to avoid unnecessary surgery

Abstract: Systemic therapy with corticosteroids is an effective and appropriate treatment option for IGM. It can provide complete disease resolution and prevent recurrence in the long term. A multidisciplinary approach including specialists in the fields of both general surgery and infectious diseases is essential for the diagnosis, treatment and follow-up of IGM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 54 publications
3
41
0
5
Order By: Relevance
“…According to literature, IGM typically affects parous females in the reproductive age group (1,12,13,(17)(18)(19). These findings were confirmed in our study, although there were exceptions.…”
Section: Discussionsupporting
confidence: 91%
“…According to literature, IGM typically affects parous females in the reproductive age group (1,12,13,(17)(18)(19). These findings were confirmed in our study, although there were exceptions.…”
Section: Discussionsupporting
confidence: 91%
“…There is controversy regarding the treatment of IGM patients. Studies have reported that systemic steroid treatment is very effective treatment option . However, long‐term high‐dose administration has numerous side effects .…”
supporting
confidence: 83%
“…There is still considerable controversy over definitive treatment of GM. Treatment options include medical management with antibiotics, steroid therapy and immunosuppressive agents, as well as more invasive approaches such as surgical excision and abscess drainage 6. Much of the recent literature has found corticosteroid therapy to be an effective means of GM resolution with a smaller chance of recurrence 3 5–7.…”
Section: Discussionmentioning
confidence: 99%